2003
DOI: 10.1161/01.res.0000097263.10220.0c
|View full text |Cite
|
Sign up to set email alerts
|

TRPV2 Is a Component of Osmotically Sensitive Cation Channels in Murine Aortic Myocytes

Abstract: Abstract-Changes in membrane tension resulting from membrane stretch represent one of the key elements in blood flow regulation in vascular smooth muscle. However, the molecular mechanisms involved in the regulation of membrane stretch remain unclear. In this study, we provide evidence that a vanilloid receptor (TRPV) homologue, TRPV2 is expressed in vascular smooth muscle cells, and demonstrate that it can be activated by membrane stretch. Cell swelling caused by hypotonic solutions activated a nonselective c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
364
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 452 publications
(374 citation statements)
references
References 36 publications
8
364
0
2
Order By: Relevance
“…Several vanilloid subtypes have been shown to be important mediators of vascular tone, cerebral blood flow, neointimal hyperplasia, and pulmonary hypertension 11, 12, 13. Expression of the transient receptor potential vanilloid 2 (TRPV2) channel was noted in abundance in murine myocardial tissue, specifically in the left ventricle 14.…”
Section: Introductionmentioning
confidence: 99%
“…Several vanilloid subtypes have been shown to be important mediators of vascular tone, cerebral blood flow, neointimal hyperplasia, and pulmonary hypertension 11, 12, 13. Expression of the transient receptor potential vanilloid 2 (TRPV2) channel was noted in abundance in murine myocardial tissue, specifically in the left ventricle 14.…”
Section: Introductionmentioning
confidence: 99%
“…It forms a Ca 2+ -conducting cation channel and was first found in sensory ganglia to be activated by heat (Caterina et al, 1999) and in aortic myocytes by cell swelling, the latter suggesting a role in osmoregulation (Muraki et al, 2003). TRPV2 channels are expressed both peripherally and centrally; their physiological functions in the brain, however, are not well understood (Ramsey et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Narayanan et al [47] demonstrated that TRPP2 was expressed in SMCs of resistance-size cerebral arteries and contributed to the myogenic response. One member of TRPV subfamily, TRPV2, was found to be expressed in mouse aortic, mesenteric and basilar arterial myocytes and could be activated by membrane stretch and hypotonic stimulation [48]. Whether TRPV2 is involved in the generation of myogenic tone remains to be elucidated.…”
Section: Trp Channels Participate In Vasoconstrictionmentioning
confidence: 99%